Purification and Properties of Urease Derived from Hydrated Seeds of Jack Bean, Canavalia ensiformis (L) DC. - Sehgal, Prem P. (1966)
Urease from jack bean meal and hydrated seeds has been obtained in 25 to 33% yield with specific activity in the range of 1000 to 1070 units/mg protein. A purification of 100 to 130-fold was achieved from meal and fully soaked seeds. Use of β-mercaptoethanol and EDTA was found essential to obtain this high yield and purity. Amino acid analysis showed all 18 amino acids commonly found in proteins. Electrophoresis of urease from soaked seeds (specific activity: 1025 units/mg protein) on a starch-gel block showed 2 peaks. Upon ultracentrifugation of urease samples having a low specific activity (less than 25% pure), the major portion of the urease was probably present in a peak having a sedimentation value of 11 to 12. With relatively pure samples (55-100% pure). S values in the range of 18 to 20 and 24 to 26 were obtained. Usually the purest samples of urease tested without any prior storage lacked the 24 to 26 S peak or the higher polymeric forms. The percentage areas under none of the ultracentrifuge peaks corresponded to the percentage purity of the sample analyzed. It is argued that the physical state of urease in the cell when associated with other seed proteins is as yet uncertain. In crude extracts, a portion of urease exists in a 12 S form but so far data on its origin and specific activity in relation to other species of urease are not available.